Beyond ethnicity: historical states and modern conflict. (December 2022) - Wishman, Marius; Butcher, Charles
Historical states, be they sprawling empires or nominal vassal states, can make lasting impressions on the territories they once governed. We argue that more historical states located within the borders of modern states increase the chance of civil conflict because they (1) created networks useful for insurgency, (2) were symbols of past sovereignty, (3) generated modern ethnic groups that activated dynamics of ethnic inclusion and exclusion, and (4) resisted western colonialism. Using new global data on historical statehood, we find a robust positive association between more historical states inside a modern state and the rate of civil conflict onset between 1946 and 2019. This relationship is not driven by common explanations of state formation that also drive conflict such as the number of ethnic groups, population density, colonialism, levels of historical warfare, or other region-specific factors. We also find that historical states are more likely to be conflict inducing when they are located far from the capital and in poorer countries. Our study points to unexplored channels linking past statehood to modern-day conflict that are independent of ethno-nationalist conflict and open possibilities for a new research agenda linking past statehood to modern-day conflict outcomes.